Describing the evolution of landscape in Karlovassi basin (Samos, Greece). Introduction of an algorithm to analyze the temporal process. - Vaiopoulos, D.; Skianis, G.; Vassilopoulos, A.; Evelpidou, N. (COST 634 Conference ‘Off-Site Impacts of Soil Erosion and Sediment Transport’, 2007)
The Karlovassi Basin is an area that has suffered many catastrophic events such as fires or floods within the last 10 years. These intense phenomena, that take place mostly at its northern part, along with the human activities, have significantly accelerated the evolution rate of the local landforms. The result is the noticeable alteration of the geomorphological landscape within these last ten years. When dealing with landscape evolution, the time is a basic factor since it determines the intensity of the morphologic development. For this paper we used an algorithm for the temporal analysis of the changes in the landscape, because of the erosional processes. The software that has been developed to apply the algorithm is GIS based and uses the concept of the cellular automata for the geospatial calculations. For each grid cell it calculates the altitude and soil thickness of the area, based on the continuity equation, which involves parameters of different natural processes such as the weathering of rocks, the river and slope sediment yield, etc. Since time is an important factor in this equation, each parameter is characterized as time constant or time dependent. The temporal variation of the physical process parameters is expressed by simple mathematical expressions, which may represent time constant values, as well as abrupt, smooth or periodical variations with time. This algorithm may support the local authorities in decision making issues, since it may identify the areas that require protection against the intense physical phenomena of the last years. Moreover, it may be useful in geomorphological and environmental research, concerning the way that some landforms evolve.